Green vehicle adoptions and its impediments: a bibliometric review / Zanariah Zakaria, Ahmad Razi Ramli and Norashikin Ismail - Zakaria, Zanariah; Ramli, Ahmad Razi; Ismail, Norashikin (UiTM Cawangan Johor, 2024)
A green vehicle produces considerably lower emissions than conventional internal combustion engine vehicles, playing a crucial role in fulfilling global commitments to combat climate change. Despite its environmental benefits, consumer adoption is far below expectations. This study addresses this issue by exploring recent publications that highlight challenges in the adoption of green vehicles. The paper aims to analyse and present findings from published documents on green vehicles, utilizing data sourced from the Scopus database. To this end, this paper contributes to the extant literature on green vehicle adoption and its impediments by assessing the publication trends and network visualization leveraging the bibliometric analysis method. Meanwhile, key research clusters are outlined and visualized to analyse the underlying knowledge structure. The 347 articles collected from the Scopus database were later analysed using bibliometric tools, VOSviewer, and Harzing’s Publish or Perish. The results presented in this paper assist researchers with a structured understanding and knowledge of green vehicle adoption research and its impediments.